Antiviral activity of nitazoxanide against pseudorabies virus infection in vitro - Tan, Lei; Zhu, Pei; Getu, Zhaori; Yang, Xi; Zheng, Shiling; Duan, Yuqing; Wang, Jinping; Zhou, Yi; Hu, Yuyang; Wang, Yijing; Yang, Yuying; Zuo, Mengting; et al. (Frontiers in Veterinary Science, 2025)
Pseudorabies (PR), an infectious disease caused by pseudorabies virus (PRV), has been responsible for substantial economic losses within the global swine industry. However, effective control measures and vaccines against PRV remain limited, thereby underscoring the necessity for the development of innovative antiviral agents targeting PRV. Nitazoxanide (NTZ) is an FDA-approved anthelminthic drug, has shown efficacy in inhibiting a variety of viral infections. This study aims to evaluate the antiviral properties of NTZ against PRV infection in vitro. The findings demonstrated that NTZ treatment significantly inhibited PRV infection in a dose-dependent manner in both PK15 and Vero cell lines, with the primary inhibitory effect occurring during the viral replication phase, rather than during the attachment, entry, or release phases of the virus. Subsequent RNA-Seq analysis revealed that cellular signaling pathways related to oxidative stress were implicated in the antiviral efficacy of NTZ against PRV infection. In conclusion, our findings implicate that NTZ effectively suppress PRV infection in vitro, suggesting its potential as a promising antiviral candidate for the clinical interventions in Alphaherpesvirinae infections.